Criteria for the formation of spiritual and moral qualities of the personality of mixed martial arts athletes - Emelyanenko, F.V.; Kondakov, V.L.; Kormakova, V.N.; Kopeikina, E.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to assess the level of formation of morality of young people involved in MMA. Methods and structure of the study. During the experiment, a theoretical analysis and generalization of scientific data were carried out, as well as psychological diagnostics of athletes, in which 41 people (38 boys and three girls) aged 16-24 years old took part. For the diagnosis were used: "Diagnostics of moral self-esteem" (L.N. Kolmogortseva); "Study of Tolerance" and "Scale of Conscientiousness" (V.V. Melnikov, L.T. Yampolsky); "Personal aggressiveness and conflict" (E.P. Ilyin, P.A. Kovalev). The study took place on the basis of the sports school of the Olympic reserve named after Alexander Nevsky (Stary Oskol). Results and conclusions. The majority of those involved in MMA have a level of self-esteem of moral qualities "below average" - 53.66% (according to the method "Diagnostics of moral self-esteem"); 58.54% of MMA athletes are characterized by an average level of tolerance, respect for other people's opinions and tolerance (according to the "Tolerance Study" methodology); 53.67% of athletes have the level of conscientiousness (according to the “Conscientiousness Scale” method) “below average”; the vast majority (85.38%) of MMA athletes had a low level of “positive aggression” and a high level (95.13%) of “negative aggression”; the majority of athletes (60.98%) had a level of conflict "above average" (according to the method "Personal aggressiveness and conflict"). Thus, the majority of athletes aged 16-24 involved in MMA showed an insufficient level of morality. Scientific substantiation and development of a program for educating the morality of a person and an algorithm for its implementation in the MMA training system are needed.